A thematic review on Industrialised Building System (IBS) publications from 2015-2019: analysis of patterns and trends for future studies of IBS in Malaysia - Mohd Noor, Mohd Zairul (Universiti Putra Malaysia Press, 2021)
IBS has been theoretically and practically proven to improve the construction delivery apart from reducing the lead of time and cost throughout its supply chain. Under the Malaysian Construction Industry Transformation Programme (CITP) 2016-2020, it is stated that the government is accelerating the adoption of IBS through mechanisation and modern practices. Despite the government’s initiative, there have been relatively small amounts of materials published discussing the patterns in IBS publications in Malaysia and what the future holds for IBS. This paper explores a thematic review of the literature regarding new definitions and patterns that juxtaposes IBS in the construction industry in Malaysia from 2015 till 2019 by using the thematic review. The findings from the code-to-document analysis using ATLAS.ti 8 found that the patterns and trends on IBS from the year 2015 to 2019. This paper contributes to analysing the patterns and trends of IBS by identifying the thematic code within IBS publications for recommendations of future studies on IBS in Malaysia.